Understanding carbon trading: Effects of delegating CO2 responsibility on organizations' trading behaviour. (3rd April 2017) - Rodriguez Lopez, Juan Miguel; Engels, Anita; Knoll, Lisa
Abstract : The establishment of a carbon market assumes that there is an effective means of transforming price information into technical carbon reduction measures. However, empirical evidence reveals that the links between price information and carbon management strategies are far from obvious. To understand how delegating CO2 responsibility affects CO2 trading behaviour, this article proposes a neo-institutionalist approach to answering the question of why companies became sellers, buyers or a combination of both during phase I of the European Emissions Trading Scheme (EU ETS). Original data from a survey on companies that participated in this scheme were collected and analysed. It was assumed that the trading scheme offered two ways to delegate decisions regarding emissions trading: decoupling from technical knowledge and financialization (i.e. delegating to financial departments) or coupling using technicalization (i.e. delegating to manufacturing departments). The results support the hypothesis that a company that adopts a decoupling strategy is more likely to buy certificates to fulfil their emissions targets. Adopting a coupling strategy indicates that a company is more likely to become a seller, all else equal. Professional identity is the theoretical basis for this relationship. Delegating carbon management to different departments represents either a stronger coupling or a stronger decoupling from core technological processes. Policy relevance The transaction data from phase I of the EU ETS open new questions and possibilities regarding the reasons that drive selling and buying in companies. It is important to look not only at the traditional sources of transaction costs, but rather also at the reasons for these tensions. One important source is the professional education of the people in charge of the EU ETS. Tailored information that directly addresses the different professional backgrounds of managers working in both financial departments and more technical departments might help to lower these types of transaction costs. In today's context, important emitter countries, such as China and Korea, have launched their own emissions markets, copying many aspects of the EU ETS. For the positive development of these markets and as a way of establishing a global emissions market, these new schemes should learn from the EU ETS experience.